Potential of Hotong Flour (Setaria italica (L.) Beauv) from Buru Island in Reducing Blood Cholesterol Levels in Wistar Rats with Diabetes Mellitus - Mose, Windi; Wael, Syahran; Salmawati, Mimi; Wahyudi, Didik; Astuti, Pudji (Universitas Pattimura, 2024)
Hotong flour (Setaria italica) can be used as a functional food as therapy in the treatment of diabetes mellitus by reduce cholesterol levels in the blood. Hotong is a rice-like food crop that is usually consumed by the people of Buru Island. Hotong seeds have quite high nutritional content, namely containing 11.18% protein, 2.36% fat, 73.36% carbohydrates, 11.78% water, and 1.32% ash. The energy produced per 100 grams of hotong seeds is 359 calories. Hotong plants can be used as an alternative commodity in a carbohydrate-producing food diversification program. This study aims to determine the potential dose of hotong flour in treating diabetes mellitus by reducing cholesterol levels in the blood of rat. This research used 24 wistar rats animals which were divided into 6 groups which were given hotong flour for 21 days and the cholesterol levels were evaluated on the 7th, 14th, and 21st day. Determination of rat blood cholesterol levels using the enzymatic method. Hotong flour can reduce blood sugar levels at doses of 1 g/kg bw and 1.5 g/kg bw in rat that have been made diabetic by examination on days 7, 14 and 21 days.